Distribution of the root system of peach palm under drip irrigation - Adriano da Silva Lopes; Fernando Braz Tangerino Hernandez; José Alves Júnior; Gabriel Queiroz de Oliveira (Acta Scientiarum. Agronomy, 2014)
The incorporation of technologies has resulted in increased productivity and the more rational management of peach palm, with irrigation being an important tool for certain regions. Thus, studies leading to proper crop management are extremely important, such as the estimate of the effective depth of the root system, which is indispensable for proper irrigation management. The objective of this study was to evaluate the effects of different irrigation depths, as applied by drip irrigation, on the distribution of the root system of peach palm. This experiment was conducted in Ilha Solteira, São Paulo State, Brazil, with drip irrigation, with the two systems (flow of 0.0023 m3 h-1) consisting of four irrigation treatments corresponding to 0, 50, 100 and 150% of Class ‘A’ pan evaporation. After five years, an analysis of the Bactris gasipaes root system was performed at a distance of 0.0, 0.5 and 1.0 meters from the trunk, collecting sampling at two depths (0.0 to 0.3 m and 0.3 to 0.6 m) via the auger method (volumetric analysis). We concluded that the effective depth of the root system used for irrigation management should be a maximum of 0.3 meters.